PENGARUH PENERAPAN PRINSIP-PRINSIP MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA - Putria Hidayatullah, Syafwatul (Graduate Program Magister Manajemen Pendidikan, 2018)
This research examined the influence of implementation the principles of teaching to studentsâ learning outcome in SMK Muhammadiyah 1 Palembang. The method used was quantitative correlation. The instruments were questionnaires which distributed to 63 samples and documentation to obtain the data score of MID Semester in academic year 2017-2018. Data analysis used product moment analysis and ttest. Based on the researchers analysis, the score of rcount obtained from the calculation was greater than the score of rtable (0,455> 0,248), while the calculation of ttest,tcount score obtained was greater than ttable (3.992> 1.670), it can be concluded that the implementation the principles of teaching gave a significant effect on studentsâ learning outcomes.